Strain Localization at Volcanoes Undergoing Extension: Investigation of Long‐Term Deformation at Krafla and Askja Volcanic Systems in North Iceland - Chiara Lanzi; Freysteinn Sigmundsson; Michelle Maree Parks; Halldór Geirsson; Vincent Drouin (Geophysical Research Letters)
Abstract Volcanoes in extensional environments may show gradual subsidence over decades during quiescent periods, due to various processes such as magma withdrawal, cooling, contraction, plate spreading and viscoelastic response. If significant rheological anomalies reside in volcano roots, due to the presence of magma and hot rock, they can influence the style of deformation. We use Finite Element Method (FEM) models to explore how strain localization due to extension can lead to volcano deflation. We apply rheological models comprising an elastic layer overlying a viscoelastic domain and include local up‐doming regions of low viscosity material beneath volcanic centers. The models reveal a localized subsidence above the rheological anomaly, influenced by the tectonic extension, and by the up‐doming volume and its viscosity. The models suggest that plate divergence may account for 4–5 mm/yr of observed subsidence at Krafla and Askja volcanic systems (KVS and AVS, respectively) in North Iceland.